Beneficial Effects of Neurotrophin-4 Supplementation During in vitro Maturation of Porcine Cumulus-Oocyte Complexes and Subsequent Embryonic Development After Parthenogenetic Activation - Kim, Mirae; Hwang, Seon-Ung; Yoon, Junchul David; Lee, Joohyeong; Kim, Eunhye; Cai, Lian; Kim, Gahye; Choi, Hyerin; Oh, Dongjin; Hyun, Sang-Hwan (Frontiers in Veterinary Science, 2021)
Neurotrophin-4 (NT-4) is a neurotrophic factor that plays an important role in follicular development and oocyte maturation. However, it is not yet known whether NT-4 is related to oocyte maturation and follicular development in pigs. This study aims to investigate the effects of NT-4 supplementation during in vitro maturation (IVM) of porcine oocytes and subsequent embryonic development after parthenogenetic activation (PA). First, NT-4 and its receptors (TrkB and p75NTR) were identified through fluorescent immunohistochemistry in porcine ovaries. NT-4 was mainly expressed in theca and granulosa cells; phospho-TrkB and total TrkB were expressed in theca cells, granulosa cells, and oocytes; p75NTR was expressed in all follicular cells. During IVM, the defined maturation medium was supplemented with various concentrations of NT-4 (0, 1, 10, and 100 ng/mL). After IVM, the nuclear maturation rate was significantly higher in the 10 and 100 ng/mL NT-4 treated groups than in the control. There was no significant difference in the intracellular reactive oxygen species levels in any group after IVM, but the 1 and 10 ng/mL NT-4 treatment groups showed a significant increase in the intracellular glutathione levels compared to the control. In matured cumulus cells, the 10 ng/mL NT-4 treatment group showed significantly increased cumulus expansion-related genes and epidermal growth factor (EGF) signaling pathway-related genes. In matured oocytes, the 10 ng/mL treatment group showed significantly increased expression of cell proliferation-related genes, antioxidant-related genes, and EGF signaling pathway-related genes. We also investigated the subsequent embryonic developmental competence of PA embryos. After PA, the cleavage rates significantly increased in the 10 and 100 ng/mL NT-4 treatment groups. Although there was no significant difference in the total cell number of blastocysts, only the 10 ng/mL NT-4 treatment group showed a higher blastocyst formation rate than the control group. Our findings suggest that supplementation with the 10 ng/mL NT-4 can enhance porcine oocyte maturation by interacting with the EGF receptor signaling pathway. In addition, we demonstrated for the first time that NT-4 is not only required for porcine follicular development, but also has beneficial effects on oocyte maturation and developmental competence of PA embryos.